2013
DOI: 10.1007/s40167-013-0001-5
|View full text |Cite
|
Sign up to set email alerts
|

Medial prefrontal cortex differentiates self from mother in Chinese: evidence from self-motivated immigrants

Abstract: Findings from neuroimaging studies suggest that the medial prefrontal cortex (MPFC) differentiates between self and mother in participants from Western cultures, but not in Chinese participants. However, previous research suggests that self-motivated immigrants possess more independent self-construal styles. Thus, it is possible that their independent self-construals might be reflected at the neural level. In the present study, we examined the contribution of the MPFC to self and close other-referential proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 34 publications
(48 reference statements)
5
29
0
Order By: Relevance
“…Based on the findings from our first study (Chen et al, 2013), both of the MPFC and PCC showed greater activity when adjectives were presented in Chinese than in English, suggesting that adjectives presented in Chinese elicited greatest activity in the MPFC and PCC. As a result, in the present study, we restricted the second-level analysis to the conditions where stimuli were presented in Chinese.…”
Section: Methodsmentioning
confidence: 95%
See 4 more Smart Citations
“…Based on the findings from our first study (Chen et al, 2013), both of the MPFC and PCC showed greater activity when adjectives were presented in Chinese than in English, suggesting that adjectives presented in Chinese elicited greatest activity in the MPFC and PCC. As a result, in the present study, we restricted the second-level analysis to the conditions where stimuli were presented in Chinese.…”
Section: Methodsmentioning
confidence: 95%
“…Among these twenty-nine participants, twelve of them were previously reported in Chen et al’s study (Chen et al, 2013). All participants were right-handed with no history of neurological problems, and had normal or corrected-to-normal vision.…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations